Acute Toxicity of Intravenously Administered Titanium Dioxide Nanoparticles in Mice - Xu, Jiaying (Public Library of Science, 2013)
BACKGROUND: With a wide range of applications, titanium dioxide (TiO(2)) nanoparticles (NPs) are manufactured worldwide in large quantities. Recently, in the field of nanomedicine, intravenous injection of TiO(2) nanoparticulate carriers directly into the bloodstream has raised public concerns on their toxicity to humans. METHODS: In this study, mice were injected intravenously with a single dose of TiO(2) NPs at varying dose levels (0, 140, 300, 645, or 1387 mg/kg). Animal mortality, blood biochemistry, hematology, genotoxicity and histopathology were investigated 14 days after treatment. RESULTS: Death of mice in the highest dose (1387 mg/kg) group was observed at day two after TiO(2) NPs injection. At day 7, acute toxicity symptoms, such as decreased physical activity and decreased intake of food and water, were observed in the highest dose group. Hematological analysis and the micronucleus test showed no significant acute hematological or genetic toxicity except an increase in the white blood cell (WBC) count among mice 645 mg/kg dose group. However, the spleen of the mice showed significantly higher tissue weight/body weight (BW) coefficients, and lower liver and kidney coefficients in the TiO(2) NPs treated mice compared to control. The biochemical parameters and histological tissue sections indicated that TiO(2) NPs treatment could induce different degrees of damage in the brain, lung, spleen, liver and kidneys. However, no pathological effects were observed in the heart in TiO(2) NPs treated mice. CONCLUSIONS: Intravenous injection of TiO(2) NPs at high doses in mice could cause acute toxicity effects in the brain, lung, spleen, liver, and kidney. No significant hematological or genetic toxicity was observed.